The great air race : glory, tragedy, and the dawn of American aviation - Lancaster, John (Journalist) (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2023)
Reclaiming one of the most important moments in American aviation history, this incredible, untold story recounts the transcontinental air race of October 1919, which riveted a nation as the aviators pioneered the first coast-to-coast air route, despite much drama and tragedy.